Exploring the Relationship Between ESG Performance and Green Bond Issuance - Wang, Shanshan; Wang, Derek (Frontiers in Public Health, 2022)
As an important part of green financial instruments, green bonds have become increasingly popular in recent years. This study employs green bond issuance as a proxy to measure investors’ recognition on firm’s sustainable activities by linking between literatures on ESG and financial performance and those on green bond issuing. This study innovatively creates the datasets by combining the ESG performance of Chinese listed companies with their green bond issuance from 2016 to 2020 based on the Wind and CSMAR databases and examines the relationship between the performance of ESG dimensions and green bond issuance from the perspective of listed firms in the emerging market. The results indicate that decent ESG practices not only increase the propensity in green bond issuance by listed firms but also help them issue more green bond. More specifically, we found the evidence to support this finding from every dimension of these sustainable practices. However, this paper identifies the negative effect of financial performance in issuing green bond when combining the effect of ESG performance.